2015
DOI: 10.1074/jbc.m115.652339
|View full text |Cite
|
Sign up to set email alerts
|

FACT Proteins, SUPT16H and SSRP1, Are Transcriptional Suppressors of HIV-1 and HTLV-1 That Facilitate Viral Latency

Abstract: Background: FACT proteins SUPT16H and SSRP1 are identified as host factors that restrict HIV-1 replication. Results: Biochemical and genetic evidences that SUPT16H and SSRP1 affect HIV-1/HTLV-1 transcription and latency are provided. Conclusion: SUPT16H and SSRP1 suppress transcription of HIV-1/HTLV-1, and their presence may promote HIV-1 latency. Significance: Identification of host factors necessary for HIV-1 latency is critical, which may benefit the development of novel HIV-1 latency-reversing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 73 publications
3
54
0
Order By: Relevance
“…VSV-G pseudotyped HIV-1 NL4–3 luciferase virus (HIV-1 Luc) or retroviruses expressing HIV-1 Tat (pQCXIP-Tat) were created as described previously (Huang et al, 2015; Power et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…VSV-G pseudotyped HIV-1 NL4–3 luciferase virus (HIV-1 Luc) or retroviruses expressing HIV-1 Tat (pQCXIP-Tat) were created as described previously (Huang et al, 2015; Power et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…After 24 hr, cells were collected and subjected to RNA extraction (RNeasy mini kit, QIAGEN), cDNA synthesis (iScript™ cDNA Synthesis Kit, Bio-Rad), and qPCR analysis using the iTaq™ Universal SYBR® Green Supermix (Bio-Rad) as described previously (Huang et al, 2015; Zhu et al, 2012). We used initiation primers (Ini) targeting bp 10–59 of HIV-1 transcript, proximal primers targeting bp 29–180 of HIV-1 transcript, intermediate primers targeting bp 836–1015 of HIV-1 transcript, distal primers targeting bp 2341–2433 of HIV-1 transcript, and GAPDH primers for normalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Huang et al, using RNAi functional genomic screens, demonstrated that individual proteins from the FACT complex act as transcriptional repressors of HIV [138]. In this study, Tat was shown to recruit the FACT complex to the HIV-1 LTR promoter by interacting with SUPT16H [138].…”
Section: Host Factors Influencing Hiv-1 Latencymentioning
confidence: 91%
“…However, the exact mechanism of inhibition by FACT is not known and could be different from a simple block between Tat and CycT1. Indeed, depletion of FACT in the U1 latent cell line, which contains a Tat-defective H13L mutant impairing P-TEFb binding, also lead to the activation of both transcription initiation and elongation, suggesting another unknown mechanism [138, 139]. Lastly, FACT seems to have a general role on retrovirus silencing since HTLV-1 Tax-dependent transcription was also affected [138].…”
Section: Host Factors Influencing Hiv-1 Latencymentioning
confidence: 99%